Menghujat dan Menista di Media Sosial Perspektif Hukum Islam - Arif Alfani; Hasep Saputra (Institut Agama Islam Negeri Curup, 2019)
This paper aims to examine blasphemy phenomena on social media which are analyzed descriptively with the approach of Islamic law. This analysis was then developed on two issues, how the phenomenon of insulting and blasphemous actions in social media, how Islamic law perspective on insulting and blasphemous actions. The reality of each user, obscenities seems to have become a compulsory song that must be sung with enthusiasm in order to berate, blaspheme, and even sometimes provoke so that it leads to anarchy. The phenomenon of mutual blasphemy on social media does not only occur at the level of the political elite, but has taken place in laymen. Media, which should be a positive center for information and communication, has turned into an arena for arguments that are far from polite. The method used in this research is library research, namely research conducted by collecting magazines, journals and books and utilizing the internet to collect data related to research. From this research method it is known that with electronic media anyone can connect without face to face. This is certainly good news, but keep in mind that behind the ease of interaction through social media there are consequences. Considering that there have been many parties involved in criminal matters violating electronic transactions that have caused mischief and blasphemy.